Development of Digital Booklet Teaching Materials the Battle of Sunda Straits 1942 Based on Local History at SMAN 1 Ciomas - Magla, Lulu; Fadillah, Moh. Ali; Maryuni, Yuni (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research is motivated byThe problem with the school's objects is the lack of varied teaching materials and knowledge about local history material that is not widely known.To overcome these problems, the teaching materials offered by the researcher are teaching materials in the form of digital booklets containing a historical event in the Sunda Strait. The type of research used is R&D (Research and Development) research using the ADDIE model (analysis, design, development, implementation, evaluation). Based on the assessment of the feasibility of the material expert getting a score of 91%, the language expert getting a score of 98%, and the media expert getting a score of 88%, then the results were obtained that the three expert validators gave an assessment in the category of